Stimulus-driven liquid metal and liquid crystal network actuators for programmable soft robotics. Issue 9 (5th July 2021) - Lv, Pengfei; Yang, Xiao; Bisoyi, Hari Krishna; Zeng, Hao; Zhang, Xuan; Chen, Yuanhao; Xue, Pan; Shi, Shukuan; Priimagi, Arri; Wang, Ling; Feng, Wei; Li, Quan
Abstract : Shape-programmable soft actuators are developed through the integration of electrically conductive liquid metals with shape-morphing liquid crystal networks. Their applications in light-fueled oscillator, crawler and programmable robotic Shadow Play are demonstrated. Abstract : Sophisticated soft matter engineering has been endorsed as an emerging paradigm for developing untethered soft robots with built-in electronic functions and biomimetic adaptation capacities. However, the integration of flexible electronic components into soft robotic actuators is challenging due to strain mismatch and material incompatibilities. Herein, we report a general strategy to integrate electrically conductive liquid metals (LMs) and shape-morphing liquid crystal networks (LCNs) towards multifunctional and programmable soft robotics. A unique colloidal LM ink with superior adhesion and photothermal conversion efficiency was judiciously designed and fabricated by ultrasonicating LMs and miniature carboxylated gold nanorods (MiniGNR-COOH) in an aqueous suspension of biological bacterial cellulose. The designed nanocellulose-based colloidal LM ink is used for shape-deformable and electrically conductive LM–LCN soft robots that can be electro- and photo-thermally actuated. As proof-of-concept demonstrations, we present a light-fueled soft oscillator, an inchworm-inspired soft crawler and programmable robotic Shadow Play exhibiting multifunctional controllability. The strategy disclosed here could open up a new technological arena for advanced multifunctional soft materials with potential utility in bioinspired soft machines, integrated soft electronics, human–computer interaction and beyond.